cGAS Restricts PRRSV Replication by Sensing the mtDNA to Increase the cGAMP Activity - Liu, Xiao-Na; Li, Li-Wei; Gao, Fei; Jiang, Yi-Feng; Yuan, Wan-Zhe; Li, Guo-Xin; Yu, Ling-Xue; Zhou, Yan-Jun; Tong, Guang-Zhi; Zhao, Kuan (Frontiers in Immunology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an RNA virus that causes great economic losses globally to the swine industry. Innate immune RNA receptors mainly sense it during infection. As a DNA sensor, cyclic GMP-AMP synthase (cGAS) plays an important role in sensing cytosolic DNA and activating innate immunity to induce IFN-I and establish an antiviral cellular state. In contrast, the role of innate immune DNA sensors during PRRSV infection has not been elucidated. In this study, we found that cGAS facilitates the production of IFN-β during PRRSV infection. Western blot and virus titer assays suggested that cGAS overexpression suppressed the replication of multiple PRRSV strains, while knockout of cGAS increased viral titer and nucleocapsid protein expression. Besides, our results indicated that the mitochondria were damaged during PRRSV infection and leaked mitochondrial DNA (mtDNA) into the cytoplasm. The mtDNA in the cytoplasm co-localizes with the cGAS, and the cGAMP activity was increased when the cGAS was overexpressed during PRRSV infection. Furthermore, the cGAMP also possesses an anti-PRRSV effect. These results indicate for the first time that cGAS restricts PRRSV replication by sensing the mtDNA in the cytoplasm to increase cGAMP activity, which not only explains the molecular mechanism by which cGAS inhibits PRRSV replication but also provides research ideas for studying the role of the cGAS-STING signaling pathway in the process of RNA virus infection.